The El-Amarna correspondence : a new edition of the cuneiform letters from the site of El-Amarna based on collations of all extant tablets - Rainey, Anson F., 1930-2011; Schniedewind, William M. (Handbook of Oriental Studies. Section 1 The Near and Middle East, 2014)
The El-Amarna Correspondence offers a completely new edition of the Amarna Letters based on personal inspection and reading of all the extant tablets. This edition includes new transcriptions and a translation along with an extensive introduction and glossary of the Amarna Letters.